Increased oxidative stress and cancer biomarkers in the ventral prostate of older rats submitted to maternal malnutrition - Portela, Luiz M. F. [UNESP]; Santos, Sergio A. A. [UNESP]; Constantino, Flavia B. [UNESP]; Camargo, Ana C. L. [UNESP]; Colombelli, Ketlin T. [UNESP]; Fioretto, Matheus N. [UNESP]; Barquilha, Caroline N. [UNESP]; Perico, Larissa L. [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Scarano, Wellerson R. [UNESP]; Zambrano, Elena; Justulin, Luis A. [UNESP] (Elsevier B.V., 2021)
The concept of Developmental Origins of Health and Disease (DOHaD) states that exposure to malnutrition early in life increase the incidence of non-communicable chronic diseases throughout the lifespan. In this study, a reduction in serum testosterone and an increase in estrogen levels were shown in older rats born to protein malnourished dams (6% protein in the diet) during gestation and lactation. Intraprostatic levels of reduced glutathione were decreased, while tissue expression of glutathione S-transferase pi and sulfiredoxin-1 were increased in these animals. Strong immunostaining for alfametilacil CoA racemase (AMACR), vascular endothelial growth factor-A (VEGF-A), and aquaporin-1 (AQP1) was also observed. In silica analysis confirmed commonly deregulated proteins in the ventral prostate of old rats and patients with prostate cancer. In conclusion, the increase in oxidative stress associated with an imbalance of sex hormones may contribute to prostate carcinogenesis in offspring, highlighting early-life malnutrition as a key risk factor for this malignance.
Keywords: DOHaD; Sex hormone imbalance; Oxidative stress; Prostate diseases; Maternal low protein diet; Aging